(untitled) (Педагогіка вищої та середньої школи, 2009)
At the beginning of XXI some tasks are arisen, such as: the definition of cooperation’s strategy, the elaboration of the joint approaches to "the harmonization" of the value orientations, content, forms and methods of the pedagogical education. The solution of these problems is the obligatory condition of the formation of the person of a teacher of chemistry as a high-professional specialist.